Implementasi AI Pada Sistem Enterprise Resource Planning: Systematic Literature Review - Dimas Irmansyah; Rizka Hadiwiyanti; Anindo Saka Fitri; Ashari Imamuddin (Universitas Multi Data Palembang, 2026)
The development of AI presents significant opportunities for ERP systems. While the opportunities presented by AI development are significant, organizations need to validate their implementation before implementing AI into their ERP systems. This study aims to determine how AI in ERP can improve business performance, the challenges and solutions in AI implementation, and the impact of AI implementation in ERP through a systematic literature review. The results demonstrate time, cost, and resource efficiencies through AI implementation in ERP. However, AI implementation presents challenges such as the quality and quantity of data required, architectural complexity, organizational readiness, and the model chosen for ERP implementation.